AN ANALYSIS OF LEXICAL COHESION OF ORAL TEXT IN TITOK SOCIAL MEDIA VIDEO CONTENT - Levi Febrianing; Aprilia Valentina (JURNAL LITERASI, 2022)
This research focuses on analyzing the lexical cohesion of speech texts contained in the Tiktok social media video content contained in Tiktoker Stanley Hao's account entitled Urip Kadang di Atas Kadang. In this research, the video content on Tiktoker Stanley Hao's Tiktok social media account entitled Urip Kadang di Atas Kadang is considered as a research material object. The theory used in this research is lexical cohesion theory which understands that every discourse has aspects of cohesion that are not only grammatical, but also lexical. The method used in this research is a descriptive qualitative method. Based on the analysis carried out, it was found that the content of TikTokers Stanlay Hao's video entitled Urip Sometimes Above Sometimes has grammatical cohesion between sentences in Stanley Hao's video content including; (1) reference, and (2) conjunction. The aspects of lexical cohesion in Stanley Hao's Tiktoker video content include; (1) repetition, (2) synonymy, (3) antonymy, (4) metonymy, and (5) hyponymy.